(untitled) (Research, Society and Development, 2022)
Brazil is the most affected Latin American country by cases of dengue, which causes damage to health, with varying symptoms depending on the severity of the infection. Assessing the factors that contribute to the spread of this pathology is essential to help control it. An epidemiological, descriptive and cross-sectional study was carried out, with data obtained from the Sistema de Informação de Agravos de Notificação (SINAN), on the notifications of Dengue cases in the micro-region of Castanhal, in the state of Pará, between 2016 and 2020. searched for studies from the Biblioteca Virtual da Saúde (BVS), using the Bioestat software. Variables such as sex, race, age group, education, hospitalization and evolution were analyzed. The municipality most affected by dengue was the municipality of Castanhal, due to its greater urbanization in the region and problems in this process, accentuating the spread of Dengue. As for seasonality, the months from January to May had the highest number of cases. The epidemiological profile shows a higher incidence among males, brown people, and ages between 20 and 59 years. With little recorded evolution, however 29.5% indicated cure. For schooling, the highest indicators were “Ign/Branco” and complete high school. Furthermore, 63.57% of the cases did not require hospitalization. The analysis made it possible to identify the incidence of Dengue in the region; seasonally, there is proportionality with the increase in rainfall; regarding the epidemiological profile, no statistical importance was observed for the variable “sex”. The study is limited to identifying the causes for the sudden increase in 2018, as well as the high number of “Ign/Branco” responses in some variables.